Large magnetoelectric coupling in 0.5Ba(Zr0.2Ti0.8)O3–0.5(Ba0.7Ca0.3) TiO3 film on Ni foil. (10th December 2018) - Swain, Atal Bihari; Rath, Martando; Dinesh Kumar, S; Ramachandra Rao, M S; Subramanian, V; Murugavel, P
Abstract: Lead-free, high piezocoefficient 0.5Ba(Zr0.2 Ti0.8 )O3 –0.5(Ba0.7 Ca0.3 )TiO3 film is fabricated on soft magnetic Ni foil as a substrate using a pulse laser deposition technique for the magnetoelectric studies. The x-ray diffraction analysis confirms the phase pure formation of polycrystalline ferroelectric film along with the presence of NiO formed during the high temperature growth process. The obtained lattice parameters suggest that the native oxide could favour the coherent growth of a ferroelectric layer. The film exhibits ferroelectric characteristics with a polarization value of 23 µ C cm −2 at 225 kV cm −1 . The fabricated heterostructure displayed a high magnetoelectric coupling coefficient with the maximum magnetoelectric voltage coefficient ( α 31 ) value of 1.08 V cm −1 Oe −1 at low field of 44 Oe. It is noteworthy to mention that the observed α 31 is comparable to the earlier reported toxic lead-based similar systems. The comparison between the experimental and calculated α 31 values suggests that the strain transfer percentage efficiency is around 69%, which is responsible for the observed large ME coupling. These experimental findings give a way to achieve high magnetoelectric coefficients by fabricating the oxide piezoelectric layer directly on the clamping free magnetic substrate.